2024
DOI: 10.3390/bs14010040
|View full text |Cite
|
Sign up to set email alerts
|

Academic Self-Concept Wins the Race: The Prediction of Achievements in Three Major School Subjects by Five Subject-Specific Self-Related Variables

Detlef H. Rost,
Xiaoli Feng

Abstract: The importance of self-related constructs in predicting academic achievement has been increasingly emphasized in recent decades. Typically, bivariate associations of self-related variables with achievements have been reported. Research quantifying the combined predictive power of more than two self-variables has been scarce. Moreover, except for the academic self-concept, these variables have almost always been measured across domains, i.e., without considering the specifics of individual school subjects. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 209 publications
1
5
0
Order By: Relevance
“…Positive academic self-concept contributed to better course achievement. Consistent with previous research, students who assessed their study-related skills as high showed better academic achievement [11,92,93]. Rather unexpectedly, mathematical self-concept was not related to course achievement in the programming course.…”
Section: Factors Related To Achievement In the Online Fc Programming ...supporting
confidence: 85%
“…Positive academic self-concept contributed to better course achievement. Consistent with previous research, students who assessed their study-related skills as high showed better academic achievement [11,92,93]. Rather unexpectedly, mathematical self-concept was not related to course achievement in the programming course.…”
Section: Factors Related To Achievement In the Online Fc Programming ...supporting
confidence: 85%
“…A comprehensive meta-analysis (Credé et al, 2017) comprising 88 independent samples found that PE is highly related to conscientiousness (ρ = .83). The strong overlap between grit and conscientiousness was replicated in later empirical studies, indicating that “the perseverance facet of grit cannot be separated from the common factors … underlying conscientiousness” (Schmidt et al, 2018, p. 713; see Collaco, 2018; Feng & Rost, 2019; Rost & Feng, 2024; Ponnock, et al 2020; Rimfield et al, 2016). Furthermore, contrary to Duckworth’s claims, research reviews (Christopoulou et al, 2018; Allen et al, 2021) concluded that overall grit apparently appears to be only moderately to weakly related to academic performance.…”
Section: The Concept Of Gritmentioning
confidence: 93%
“…However, further studies have shown that grit is composed of two correlated factors. Consequently, two separate scores for PE and CI have been established and measured (e.g., Cormier et al, 2019; Feng & Rost, 2019; Fong & Kim, 2021; He, Wu et al, 2021; Hein et al, 2021; Karlen et al, 2019; Larkin et al, 2023; Muenks et al, 2018; Obermeier et al, 2023; Rhodes & Giovannetti, 2021; Rost & Feng, 2024; Sigurdson & Petersen, 2018; Soleimanzadeh et al, 2024;Tortul et al, 2020; Tyumeneva et al, 2019; Xu et al, 2020; Zhao & Wang, 2023).…”
Section: The Concept Of Gritmentioning
confidence: 99%
See 2 more Smart Citations